Procedimiento en “R” para optimizar el sabor y consistencia de la mermelada de aguaymanto y berenjena - Loyaga Mendoza, Luis Pedro (2018)
In order to develop a series of steps in the R language to optimize the taste and consistency of jam obtained from aguaymanto and eggplant; this research was conducted._x000D_ Ratio were the variables aguaymanto / eggplant in the range from 1/1 to 5/1, and the percentage of pectin in the range of 0.05 to 0.8% on the response variables were the taste and consistency in jam._x000D_ A sequence of steps was used to optimize the flavor and consistency of jam obtained from aguaymanto and eggplant R Language ranging from the simple to complex._x000D_ The most appropriate values of the process variables was determined by Response Surface Methodology; using a factorial design 22 including 4 axial points and three central points; which allowed obtaining models that define the behavior of the independent variables aguaymanto / eggplant and pectin percentage dependent regarding to the consistency and taste responses proportion. The models were highly significant at (p <0.05) both the proportion and percentage of pectin by having a high coefficient of determination R2, being possible to construct surfaces answer for this free software Language "R" was used._x000D_ The most suitable conditions were a ratio of pulp aguaymanto / eggplant from 5.5 / 1 to 6.5 / 1 and pectin percentage between 0.2 and 0.6%. Obtaining values of 7.05 to 5.85 the flavor and consistency for aguaymanto jam and eggplant